Implementation of Musharakah Contract in Financing Products Working Capital at Bank Panin Dubai Syariah Branch Makassar - Auliah, Alya; Saharuddin, Saharuddin; Trimulato, Trimulato (Institut Agama Islam Negeri Metro, 2023)
The development of the Islamic finance industry continues to experience good the choice of Islamic financial products is increasingly diverse. Sharia bank financing products consist of buying and selling, leasing, and profit-sharing schemes. Financing in Islamic banks is still dominated by consumptive financing with Murabaha contracts. Islamic banks have financing products with profit-sharing schemes that can be used for productive financing. This study aims to describe the application of musyarakah contracts in working capital financing at Bank Panin Dubai Syariah Branch Makassar. As well as outlining the application of the musyarakah contract in conformity with sharia principles. The research method used is qualitative research with field research, related to musyarakah contract financing for working capital at Bank Panin Dubai Syariah Makassar. The data sources used are primary data, data obtained directly by interviews, and secondary data from data previously presented. Data collection techniques by direct interviews with parties related to musyarakah financing and through documentation from several relevant sources. The data analysis technique used is descriptive qualitative which describes the application of musyarakah contracts in working capital financing at Bank Panin Dubai Syariah. The study results show that applying a musyarakah contract for working capital is adjusted to the type of business owned by the customer. Financing intended for a project provided that both the bank and the customer contribute capital to run a business project with profits divided according to the capital contribution portion (nisbah). The application of the musyarakah contract for working capital financing at Bank Panin Dubai Syariah branch Makassar is by Sharia principles.